TECHNICAL EFFICIENCY OF SHALLOT PRODUCTION IN PRODUCTION CENTERS IN JAVA AND OUTSIDE JAVA - Lailandra, Andjani; Kusnadi, Nunung; Harmini, Harmini (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
To increase shallot production in Indonesia is faced with the issue of the dichotomy between Java and outside Java. Data shows that more than 70% of shallot harvested area is on Java, even though it is only 17% of Indonesia's total agricultural area.  This research aims to identify factors that determine shallot production and measure the technical efficiency of shallot production and its determining factors. We used survey data from the Central Bureau of Statistics in 2014, which consisted of 2,860 input-output units of shallot production on Java and 940 outside Java. Using the stochastic frontier production function, it is found that production factors of land, labor, seeds, fertilizers and pesticides significantly determine shallot production in Java and outside Java. The marginal productivity of land, labor, seeds, fertilizers and pesticides in Java is higher than outside Java. The average technical efficiency score of production outside Java is higher than in Java. However, land productivity outside Java is lower than in Java. These findings indicate that the majority of shallot farming outside Java is already at its production frontier, whereas in Java only a small portion has reached its production frontier. Technical efficiency of production is determined by season and type of land, as well as farmers' membership in farmer groups, partnerships, and cooperatives. This conclusion implies that increasing shallot production outside Java requires new technology that can increase marginal input productivity. Technology to be developed is the use of true shallot seeds, accompanied by irrigation and agricultural institutions.